Development of Online Supervision System for Industrial Education Pre-Teachers - Thanat Nonthaputha; Montree Kumngern; Piya Prasongjan; Usa Torteanchai; Nawaphol Thepnarin; Wassana Bunsong (My University, 2021)
In case of coronavirus disease starting in 2019 situations, it is a novel syndrome virus which caused due to the outbreak of highly dangerous. This virus is easily spreadable to human by human. The one of measures for prevention for the human in coronavirus disease situations that the human has been working from home and decreasing face-to-face contacted. This paper presents the development of online supervision system that instead of traditional supervision or onsite face-to-face supervision for industrial education pre-teacher students. It has been designed on web application to convenient for supervisors, mentors and pre-teacher students. They will send about report, assignment and teaching video on the system. Supervisors and mentors can comment, check the report or assignment and approve pre-teacher video teaching on the web daily or weekly. In addition, the proposed system can be decreased the expenses for official travel and a lot of papers when compare with traditional supervision or onsite face-to-face supervision.
Keywords: Education and Learning Interventions